Menunggu perubahan dari balik jeruji (Studi awal penerapan konsep pemasyarakatan) - [Tidak Terdaftar] (Kemitraan, 2007)
Menunggu perubahan dari balik jeruji (Studi awal penerapan konsep pemasyarakatan)